Human Relations Implementation in Sustaining Business Cooperation (A Case Study at PT Pan Pacific Nesia) - Puja Kharisma Nurfauziah; Ani Yuningsih; Maman Suherman (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
This study analyzes the implementation of Human Relations–based business communication in sustaining long-term cooperation with investors at PT Pan Pacific Nesia, a garment manufacturing company within a Korean business group. Operating in a dynamic, labor-intensive environment, the company faces challenges in maintaining accurate information flow and transparent reporting to its primary investor. The research aims to explain how Human Relations functions as a communication technique and relationship management strategy that supports trust-building, collaboration, and investor confidence. Human Relations theory, Relationship Management Theory, and Integrative Negotiation are used to interpret the interpersonal and relational dynamics within the communication process. A qualitative case study design within a constructivist paradigm was employed. Data were obtained through in-depth interviews, direct observation, and document analysis, with purposive sampling involving Human Relations personnel, Payroll and Accounting staff, Operations representatives, and investor delegates. The findings indicate that PT Pan Pacific Nesia implements integrated Human Relations communication practices, including routine coordination forums, transparent digital reporting, and open dialogue communication. These practices foster trust, commitment, and relationship satisfaction. The use of an integrative negotiation approach further supports mutually beneficial, long term agreements. The study concludes that strategic Human Relations communication supported by relational management and integrative negotiation principles plays a vital role in maintaining transparency, strengthening collaboration, and sustaining long term business partnerships in the garment industry.